Model Kepercayaan Kesehatan Pasien Diabetes Melitus Tipe II - Ni Made Ayu Widhiastuti; I Wayan Candra (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
Diabetes mellitus type II is one of the health problems for the community both globally, regionally, and nationally. Most patients with type II diabetes mellitus have poor illness perception (everyone's belief about their disease and how to respond to disease). The purpose of this study was to determine the health belief model in type II diabetes mellitus patients at the Mangusada Hospital. This type of research was descriptive with a case study design using a cross-sectional approach. The sample in this study was 31 people, with apurposive sampling technique. The data analysis technique was carried out descriptively. The results of the study according to the characteristics of research subjects based on age who mostly had a good health belief model were found at the age of 41-60 years as many as 19 people (100,0 %). Based on gender, 13 people (68,4%) were found to have a good health belief model, from the highest level of education, 13 people (68,4%) were found to have a good health belief model in secondary education. Based on the most occupations found to have a good health belief model as self-employed as many as 7 people (36,8%), from the longest duration of illness found to have a good health belief model of more than 6 months chronic as many as 19 people (61,3%). The results of the study from 31 research subjects who mostly had a good health belief model were 19 people (61,3 %). It can be concluded that most of the research subjects with type II diabetes mellitus have a good health belief model.